Transfer of nuclear technology obtained by the Argentine Republic as a consecuence of the contruction of the first two nuclear power stations - Quihillalt, O. J.; Grasso, H. O. (Atomic Energy Organization of Iran, 1977)
Fil: Quihillalt, O. J. Comisión Nacional de Energía Atómica; Argentina